Role of numerical modelling choices on the structural response of onshore wind turbine shallow foundations. (March 2022) - Martinelli, Paolo; Flessati, Luca; Dal Lago, Bruno; Fraraccio, Giancarlo; di Prisco, Claudio; di Prisco, Marco
Abstract: Structural modelling of wind turbine shallow foundations on granular soil strata deals with combined complex phenomena, such as soil-structure interaction, material nonlinearities, local stress concentration in both reinforced concrete foundation and soil. Numerical finite element analyses are performed employing three-dimensional elements for both concrete foundation and soil and one-dimensional elements for reinforcement. The results of the nonlinear static simulations are validated with experimental results of recent tests carried out on 1:15 scaled models having reinforcement ratios and stress conditions similar to the prototype foundations designed according to current codes. The validated modelling strategies are also applied to investigate the role of nonlinearities in both soil and concrete foundation, emphasizing the parameters and the nonlinear constitutive laws that significantly affect the foundation response. Three different reinforcement layouts are considered in both testing and simulations of the prototype: (a) complete prototype reinforcement, (b) prototype without shear reinforcement and (c) prototype without shear reinforcement and with 50% of remaining reinforcement replaced by steel fibres. A critical comparison is also made with models employing elastic two-dimensional shell finite elements lying over elastic supports, typically adopted for design purposes.